ANALISIS KONFLIK BATIN DALAM NOVEL SI LAMSIJAN KAEDANAN KARYA KI UMBARA - Ihsan Fathurrohman; Fajar Sukma Nur Alam (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze the structure, as well as the forms and causes of inner conflict in the novel Si Lamsijan Kaedanan by Ki Umbara. Inner conflict is a crucial element that significantly contributes to character development and plot progression in literary works. The research employs a descriptive qualitative method with a literary psychology approach. Data were collected through thorough reading, noting, and classifying passages related to the psychological struggles experienced by the main characters. The findings reveal that the protagonist, Lamsijan, undergoes several forms of inner conflict, including tension between his idealism and the harshness of real life, between personal desires and social norms, and moral dilemmas triggered by environmental and situational pressures. These inner conflicts shape Lamsijan into a multidimensional and realistic character, enhancing the novel’s narrative depth. Moreover, the internal struggles serve as key driving forces in the development of the storyline and the communication of the novel’s moral values. This research underscores the significance of examining characters’ psychological dimensions to gain a deeper understanding of the thematic layers and artistic merits of literary texts.